2013
DOI: 10.1371/journal.pgen.1003506
|View full text |Cite
|
Sign up to set email alerts
|

The Secretory Pathway Calcium ATPase PMR-1/SPCA1 Has Essential Roles in Cell Migration during Caenorhabditis elegans Embryonic Development

Abstract: Maintaining levels of calcium in the cytosol is important for many cellular events, including cell migration, where localized regions of high calcium are required to regulate cytoskeletal dynamics, contractility, and adhesion. Studies show inositol-trisphosphate receptors (IP3R) and ryanodine receptors (RyR), which release calcium into the cytosol, are important regulators of cell migration. Similarly, proteins that return calcium to secretory stores are likely to be important for cell migration. The secretory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 102 publications
0
17
0
Order By: Relevance
“…The pigv-1 ( qm34 ) was retrieved from an EMS screening conducted by Hekimi et al [ 25 ]. For analysis using GFP fusions, F2 progeny exhibiting pigv-1 phenotypes and carrying the markers were selected from crosses between pigv-1 ( qm34 ) and the following strains: SU93 jcIs1[ajm-1 :: gfp , unc-29(+) , rol-6p :: rol-6(su1006)] [ 46 ], SU265 jcIs17[hmp-1p :: hmp-1 :: gfp , dlg-1p :: dlg-1 :: dsRed , rol-6p :: rol-6(su1006)] [ 47 ], SU467 pIs7[pha-4p :: pm :: gfp , rol-6p :: rol-6(su1006)] [ 48 ], FT17 xnIs3[par-6p :: par-6 :: gfp , unc-119(+)] ; unc-119(ed3) III , MOT63 temIs59[pIC26 :: pkc-3] ; unc-119(ed3) III , WS4918 opIS310[ced-1p :: yfp :: act-5 :: let-858 3'UTR , unc-119(+)] [ 49 ], VJ402 fgEx1[erm-1p :: erm-1 :: gfp , rol-6p :: rol-6(su1006)] [ 33 ], ML1735 mcIs50[lin-26p :: vab-10(actin-binding domain) :: gfp , myo-2p :: GFP] [ 50 ], plag-2p :: piga-1 :: egfp -expressing strain was generated by Murata et al [ 10 ].…”
Section: Methodsmentioning
confidence: 99%
“…The pigv-1 ( qm34 ) was retrieved from an EMS screening conducted by Hekimi et al [ 25 ]. For analysis using GFP fusions, F2 progeny exhibiting pigv-1 phenotypes and carrying the markers were selected from crosses between pigv-1 ( qm34 ) and the following strains: SU93 jcIs1[ajm-1 :: gfp , unc-29(+) , rol-6p :: rol-6(su1006)] [ 46 ], SU265 jcIs17[hmp-1p :: hmp-1 :: gfp , dlg-1p :: dlg-1 :: dsRed , rol-6p :: rol-6(su1006)] [ 47 ], SU467 pIs7[pha-4p :: pm :: gfp , rol-6p :: rol-6(su1006)] [ 48 ], FT17 xnIs3[par-6p :: par-6 :: gfp , unc-119(+)] ; unc-119(ed3) III , MOT63 temIs59[pIC26 :: pkc-3] ; unc-119(ed3) III , WS4918 opIS310[ced-1p :: yfp :: act-5 :: let-858 3'UTR , unc-119(+)] [ 49 ], VJ402 fgEx1[erm-1p :: erm-1 :: gfp , rol-6p :: rol-6(su1006)] [ 33 ], ML1735 mcIs50[lin-26p :: vab-10(actin-binding domain) :: gfp , myo-2p :: GFP] [ 50 ], plag-2p :: piga-1 :: egfp -expressing strain was generated by Murata et al [ 10 ].…”
Section: Methodsmentioning
confidence: 99%
“…Double mutants of pmr-1 and a gain of function mutant of itr-1 (the worm IP 3 R orthologue) reduced lethality, and double mutants of pmr-1 and a loss-of-function mutant of itr-1 showed enhanced lethality or were not viable. In contrast, depletion with RNAi of unc-68 (the worm orthologue of RyR) considerably increased the viability of pmr-1 mutants [92]. Although difficult to explain, these findings strongly suggest that Ca 2+ signaling play a critical role in cell migration and attachment during embryogenesis.…”
Section: The Role Of the Secretory Pathway Ca 2+ Pump Atpasementioning
confidence: 94%
“…PMR1 also has an important role in embryogenesis [92], and pmr-1 mutants show important defects in cell migration and attachment that resemble the loss of skin cell adhesion observed in Hailey-Hailey disease, a dominant human disease caused by the loss of one of the copies of the SPCA1 gene [93]. Interestingly, the level of embryonic lethality could be modulated by changing the activity of IP 3 R and RyR channels, although the modulation of each of these channels produced opposite effects.…”
Section: The Role Of the Secretory Pathway Ca 2+ Pump Atpasementioning
confidence: 99%
“…Collective cell migration is an important cellular event, which is involved in many different physiological processes such as embryonic development, [1][2][3] tissue repair, [4][5][6] angiogenesis, [7][8][9] and wound healing. [10][11][12] In particular, it has been suggested that this collective behavior plays important roles in the invasion and spread of malignant cells.…”
Section: Introductionmentioning
confidence: 99%